CMOS current follower circuits - Parnklang, J.; Nanthanawanitch, W.; Titiroongruang, W. (My University, 1999)
We design current follower circuits (CF) using the CMOS transistor to substitute for the bipolar transistor circuit. The experimental result which uses Spice program found that the input and output impedance of the circuit are 5 kω and 76 Mω respectively. Moreover, the bandwidth of the circuit can be used in a wide range from 0 Hz to 4.1 MHz for CF+ and 0 Hz to 3.4 MHz and the harmonic distortion is less than 4.06% for CF+ and 4.27% for CF/sup-/. We also implement the circuit by using a commercial MOS transistor 4007, which consists of a dual complement of the CMOS transistor. The implemented circuits show that the electrical characteristics are the same as the analysis results from the Spice program.